Climate-Smart Village: Platforms for Forecasting Adaptation Action - Soriaga, Rowena; Monville-Oro, Emily; Rosimo, Magnolia; Cabriole, Marie Aislinn; Barbon, Wilson John; Ilaga, Alicia; Hellin, Jon; Gonsalves, Julian (International Institute of Rural Reconstruction, 2024)
This policy brief synthesizes lessons from five years (2018–2022) of experience in nurturing Climate-Smart Villages (CSVs) as platforms for resilience building, women’s empowerment, equity, and sustainable food systems in Southeast Asian countries. The International Institute of Rural Reconstruction (IIRR), with support from the International Development Research Center (IDRC) Canada, collaborated with farmers, local authorities, civil society actors, and national agencies to support climate-vulnerable villages in Cambodia, Myanmar, and the Philippines. Research findings and recommendations are documented in 22 knowledge products, which form the basis of this policy brief.